How does colonial heritage segment food markets? Evidence from rice consumers in Mauritania - Britwum, Kofi; Demont, Matty (Oxford University Press, 2022)
Reducing Africa’s dependence on Asian rice imports requires tailoring local rice products to food markets that are segmented by cultural heritage of ancient rice domestication and colonial heritage of more recent import substitution policies. Using experimental auctions, we examine quality upgrading and branding spillovers from Senegal by assessing the competitiveness of Senegalese vis-à-vis imported Asian rice products in an urban market in Mauritania. The Mauritanian rice market is mainly shaped by colonial heritage and is segmented into (i) elite White Hassanis, (ii) lower caste Black Hassanis, (iii) immigrants with colonial heritage, and (iv) a smaller group of immigrants with cultural heritage. While colonial heritage generally tends to incline consumers towards imported rice, local rice is preferred by Black Hassanis, older and more educated consumers, housewives, and wealthier families. This evidence can support policymakers and value chain actors in their efforts to spill over rice value chain upgrading between the Senegalese and Mauritanian river banks along the Senegal River Valley.